ANALYSIS OF FIQH MUAMALAH ON THE POTENTIAL FOR GAMBLING IN STOCK TRADING ON THE INDONESIAN STOCK EXCHANGE - Zuinan Nisa; Sa'dan, Saifuddin; Khairul Azmy (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This article aims to analyse stock trading activities on the Indonesia Stock Exchange (IDX) according to muamalah jurisprudence. The research method used is qualitative with a descriptive-analytical approach, which focuses on an in-depth understanding of the phenomenon by emphasizing its meaning and implications. This study explores the concept of muamalah jurisprudence, relevant sharia principles, and how the principles can be applied in the mechanism of stock trading in the capital market. The results of this study indicate that conducting trading practices using only technical analysis can be classified as gambling behaviour. This is because the practice contains elements of gambling and speculation which are strictly prohibited in Islam. This gambling element arises because decisions taken in trading are based on short-term price movements without considering the real conditions of the company, so that it is more similar to a game of chance. Therefore, to avoid elements of gambling and speculation that are not in accordance with sharia principles, capital market players are advised to combine technical analysis with fundamental analysis. Thus, they can understand the condition of the company more comprehensively, including financial aspects, performance and business prospects, so that the decisions taken become more rational and orderly. This step not only minimizer potential losses, but also ensures that trading activities remain within the corridor of sharia which is ethical, fair and responsible.